Morphological Features of Two Poa Species on Different Soil Types in Seminatural Grasslands - K. Szabó, Zsuzsa (Acta Agraria Debreceniensis, 2005)
The Poa pratensis L. and the Poa angustifolia L. are close relative species whose morphological features vary greatly. Our goal was to examine how the inividuals from different soil types of these species differ statistically from one another, whether the morphological features of the variant species differ significantly, and whether they keep their specific features in dissimilar habitats.The quantitative features of the populations developing on distinct soil types wich are statistically separate provide for the different phenotype forming effect of the soil types as variant habitats. There is connection between the soil types and the measurement of the ramets on every soil types. The morphometric values of P. pratensis – that are bigger in all habitats – show that this species genetically widely adapted. Significantly different morphological features were found, but because of the high environmental dependence of the morphological features and of the significantly different characteristics which reveal several overlaps between the two species, these characteristics cannot be considered as reliable identification keys.